Impact of applying the immediate process in flagrancy cases in Peru, 2016 - Málaga Enciso, Erik Robin (2017)
The purpose of this research was to measure the impact of the application of the immediate process in cases of flagrancy in Peru during the year 2016. Investigation of an applied type, not experimental cross-sectional, descriptive explanatory level. The information obtained through the questionnaire was considered the documentary analysis sheet; And the interview card. Once the phase of analysis and interpretation of the results was completed, ¡it was pointed out that the application of the immediate process in cases of flagrancy simplifies procedural and investigative acts that corroborate the existence of the crime and the criminal responsibility of the accused, gives greater speed to the Processes and timely satisfaction of the damage suffered by the victims, as well as citizen expectations.